Manipulation Impact through Metaphors in Political Discourse - R I Zaripov (Vestnik Rossijskogo universiteta družby narodov. Seriâ Lingvistika, 2014)
The article covers the metaphorical modeling in a political discourse as one of linguistic manipulation impact means. Political speech exercising a motivation function use symbols in order to link concepts which are not often even adjoined. And it’s a metaphor that plays one of leading roles in this process. Communication needs stable metaphors. It’s very important to use this linguistic means in a political discourse as it’s able to form a positive stock phrase and a negative figure. The summation of metaphors in a definitive conceptual domaine of a political discourse form part of a metaphorical model that is an universal epistemological category expressing a general discourse semantics and organizing special mentality stereotypes for a message recipient. The article is designed for students and post-graduate students specialized in philology, lecturers and professors of linguistics and foreign languages, scientists and amateurs.